The Problems of Summative Assessment in Meeting the Standardization of the Merdeka Curriculum for Islamic History and Culture Subjects at MTs Al Azhar Pagar Alam - Nuraini, Lika; Julius (The Future of Education Journal, 2025)
Summative assessment is an evaluation conducted at the end of the learning process to measure the achievement of the learning objectives of students as a basis for determining grade advancement, student graduation, or success in the learning process. This research aims to understand the issues surrounding summative assessment in fulfilling the standards of the Merdeka Curriculum for the subject of Islamic Cultural History and to explore solutions for overcoming the issues of summative assessment in meeting the standards of the Merdeka Curriculum for Islamic Cultural History (MTs) at MTs Al Azhar Pagaralam City. The methodology used is field research with a purposive sampling technique. Data were collected through interviews, observation, and documentation. The results of the study indicate that there are several standards of the Merdeka Curriculum regulations in the implementation of summative assessment that have not been met.